Corrections of diverse forms of lower limb deformities in patients with mucopolysaccharidosis type IVA (Morquio syndrome) - Ali Al Kaissi; Vladimir Kenis; Eugeniy Melchenko; Maher Ben Ghachem; Robert Csepan; Franz Grill; Rudolf Ganger (Wolters Kluwer Medknow Publications, 2016)
Background: Thoracolumbar kyphosis has been considered as the first presenting deformity and is often a key diagnostic clue noted in children with mucopolysaccharidosis (MPS) type IV (Morquio's syndrome). However, we observed that the progressive irregularities of the epiphyses of the long bones were the most prominent skeletal pathology, causing effectively the development of diverse forms of lower limbs deformities with extreme variation in age of onset. Materials and Methods: Ten patients (seven children and three adults) with an average age of 15 years have been enrolled in this study. Age of diagnosis of MPS IVA has a variable age of onset and a MISLEADING rate of severity. Hip dislocations, genu valgum, protrusio acetabuli and osteoarthritis were the most common lower limbs deformities in these patients. Clinical and radiographic phenotypes were the baseline tools of documentation. Urinary screening and genotypic characterizations have been applied accordingly. Results: Combined pelvic and femoral procedures for hip dislocation, epiphysiodeses and supracondylar osteotomy for genu valgum and hip arthroplasty for protrusio acetabuli have been performed. All patients manifested insufficient activity of N-acetylgalactosamine-6-sulphate sulphatase, an enzyme that degrades keratin sulphate and chondroitin-6 sulphate. Conclusion: The extensive clinical heterogeneity contributed significantly in the delay in establishing the diagnosis particularly in adult patients with MPS IV. The epiphyseal irregularities of the long bones and the progressive flattening pathology of MPS IV A were the reason to falsely diagnose some patients as spondyloepiphyseal dysplasia congenital and/or tarda. Proximal femoral osteotomy, realignment osteotomy and total hip arthroplasty have been performed for coxa vara, genu valgum and protrusio acetabuli, respectively, in children and adult group of patients. The importance of early diagnosis on MPS IV A is to receive enzyme replacement therapy and plan for other therapeutic measures.